Democracy and the Politics of Coronavirus: Trust, Blame and Understanding. Issue 2 (23rd June 2020) - Flinders, Matthew
Abstract: This article explores the relationship between crises and democracy through a focus on the unfolding coronavirus pandemic. Its central argument is that to interpret the current pandemic purely in terms of its epidemiology and public health implications risks overlooking its potentially more significant socio-political consequences. This is because the challenges posed by the coronavirus crisis have themselves become overlaid or layered-upon a pre-existing set of concerns regarding the performance, efficiency and capacity of democratic political structures. The aim of this article is to try and understand and warn against what might be termed a rather odd form of cross-contamination whereby the cynicism, negativity and frustration concerning politicians, political processes and political institutions that existed before the coronavirus outbreak is allowed to direct, define and automatically devalue how democratic structures are subsequently judged in terms of how they responded to the challenge. As such, this article focuses on the link between the Coronavirus crisis and the democratic crisis; or, more precisely, the risk that the Coronavirus crisis may mutate into and fuel a broader crisis of democracy.